Adjacent vs. separated placement of preposition and noun as a factor in noun inflection: The cases of Bosnian- Croatian-Serbian pazuho ‘armpit’ - Browne, Wayles (Vilnius University Open Series, 2021)
The alternations k~c, g~z, and x~s occurring before i in Bosnian-Croatian-Serbian (BCS) noun declension stem from the Second Palatalization of Velars, but are no longer phonologically conditioned. In the dative-locative singular of nouns with nominative in -a, they are favored or hindered by a combination of morphological criteria. In the dative-instrumental-locative plural of masculine nouns, they are almost exceptionless. In the same three cases of neuter nouns they occur more when the noun is directly after a preposition, less when other words intervene between the preposition and the noun, a phenomenon that has not previously been remarked in the literature. We exemplify it with the noun pazuho ‘armpit’.